Healthcare Service Quality Improvement Using ISO 9001:2015 Gap Analysis at PT Hurip Putera Husada - Muhammad Rizki Al-biruni; Sukanta; Naufal Rabbani Sumitra (Jurnal Serambi Engineering, 2026)
The implementation of the ISO 9001:2015 Quality Management System (QMS) has become an important strategy for improving healthcare service quality through a systematic and continuous management approach. However, evaluating the level of conformity with the standard remains essential to identify implementation gaps that may affect the effectiveness of the quality management system. This study aimed to evaluate the implementation of ISO 9001:2015 at Klinik Utama Pupuk Kujang using a gap analysis approach, identify conformity gaps, and formulate improvement recommendations. A descriptive quantitative approach supported by qualitative data was employed. Data were collected through direct observations, semi-structured interviews, questionnaires based on ISO 9001:2015 clauses, and document reviews. The data were analyzed by calculating the conformity level of each ISO 9001:2015 clause and supported by root cause analysis and the Plan–Do–Check–Act (PDCA) framework to develop improvement strategies. The results revealed an overall conformity level of 77.39%, indicating that the Quality Management System has been implemented at a good level. Clause 8 (Operation) achieved the highest conformity score of 81.71%, while Clause 7 (Support) obtained the lowest score of 72.00%, making it the highest priority for improvement.